INTEGRATING CUSTOMARY LAW AS LIVING LAW IN INDONESIA’S NATIONAL LEGAL SYSTEM: CHALLENGES AND INSTITUTIONAL GAPS - Panjaitan, Ananda Chrisna D.; Panjaitan, Torang Fadly (Universitas Padjadjaran, 2026)
Customary law in Indonesia remains a living system that reflects community values, social ideals, and conceptions of justice. However, its position within the national legal framework continues to generate tension, particularly due to the dominance of statutory law, which prioritizes formal rationality and legal certainty. This study aims to examine how the interaction between customary law and national law is constructed and implemented in Indonesia, as well as to identify the factors that hinder their effective integration. Using a normative legal research method based on a systematic review of secondary legal materials, this study analyses legal doctrines, statutory regulations, and relevant scholarly works concerning legal pluralism. The findings reveal that, despite formal recognition, the integration of customary law into the national legal system remains fragmented. Limitations within legal institutions, legislative frameworks, and judicial practices contribute to inconsistencies in accommodating customary law-based disputes. This study argues that the lack of clear operational mechanisms and institutional support has resulted in suboptimal legal outcomes, particularly in ensuring justice for communities governed by customary norms. By highlighting both structural constraints and potential avenues for reform, this research contributes to the discourse on legal pluralism by proposing a more coherent approach to harmonizing customary and national law, aimed at achieving justice, legal certainty, and respect for Indonesia’s diverse legal traditions.